Gaze in the military: authorial agency and cinematic spectatorship in 'drone documentaries' from Iraq. Issue 1 (2nd January 2016) - Smith, Christina M.
Abstract : Documentary films employing soldier-generated material were a popular phenomenon during the War in Iraq, as film-makers utilized soldier-captured footage and narration in their films. One of the most successful was Deborah Scranton's The War Tapes (2006). Notably, Scranton gave the soldiers cameras, and offered instructions through technology while the soldier-videographers were deployed, a technique she called a 'virtual embed.' Similar films included Bad Voodoo's War (2008), Combat Diary (2006) and This is War (2007). A central production issue was that the directors lacked access to the events as they happened because they took place on a dangerous battlefield. This paper will explore how soldier-filmed material is implemented in these documentary films. I advance the term 'Drone Documentary' as a conceptual analogy to refer both to the aesthetic style of the long-range surveillance camera and to the agentless operative gathering images and intelligence on behalf of a distanced, yet powerful controller.